Fibroblast growth factor receptor inhibitors mitigate the neuropathogenicity of Borrelia burgdorferi or its remnants ex vivo - Parthasarathy, Geetha (Frontiers in Immunology, 2024)
In previous studies, we showed that fibroblast growth factor receptors (FGFRs) contribute to inflammatory mediator output from primary rhesus microglia in response to live Borrelia burgdorferi. We also demonstrated that non-viable B. burgdorferi can be as pathogenic as live bacteria, if not more so, in both CNS and PNS tissues. In this study we assessed the effect of live and non-viable B. burgdorferi in inducing FGFR expression from rhesus frontal cortex (FC) and dorsal root ganglion (DRG) tissue explants as well as their neuronal/astrocyte localization. Specific FGFR inhibitors were also tested for their ability to attenuate inflammatory output and apoptosis in response to either live or non-viable organisms. Results show that in the FC, FGFR2 was the most abundantly expressed receptor followed by FGFR3 and FGFR1. Non-viable B. burgdorferi significantly upregulated FGFR3 more often than live bacteria, while the latter had a similar effect on FGFR1, although both treatments did affect the expressions of both receptors. FGFR2 was the least modulated in the FC tissues by the two treatments. FGFR1 expression was more prevalent in astrocytes while FGFR2 and FGFR3 showed higher expression in neurons. In the DRG, all three receptor expressions were also seen, but could not be distinguished from medium controls by immunofluorescence. Inhibition of FGFR1 by PD166866 downregulated both inflammation and apoptosis in both FC and DRG in response to either treatment in all the tissues tested. Inhibition of FGFR1-3 by AZD4547 similarly downregulated both inflammation and apoptosis in both FC and DRG in response to live bacteria, while with sonicated remnants, this effect was seen in one of the two FC tissues and 2 of 3 DRG tissues tested. CCL2 and IL-6 were the most downregulated mediators in the FC, while in the DRG it was CXCL8 and IL-6 in response to FGFR inhibition. Downregulation of at least two of these three mediators was necessary to downregulate apoptosis levels in general. We show here that FGFR inhibition can be an effective anti-inflammatory treatment in antibiotic refractive neurological Lyme. Alternatively, two biologics may be needed to effectively curb neuroinflammation and pathology in the CNS and PNS.